2012
DOI: 10.1073/pnas.1110287109
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B kinase phosphorylates and instigates degradation of p53

Abstract: Aurora B is a mitotic checkpoint kinase that plays a pivotal role in the cell cycle, ensuring correct chromosome segregation and normal progression through mitosis. Aurora B is overexpressed in many types of human cancers, which has made it an attractive target for cancer therapies. Tumor suppressor p53 is a genome guardian and important negative regulator of the cell cycle. Whether Aurora B and p53 are coordinately regulated during the cell cycle is not known. We report that Aurora B directly interacts with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 50 publications
7
148
0
2
Order By: Relevance
“…Clearly, the FBXW7-Aurora B link will be an important molecular target for rational cancer therapy. Since FBXW7 expression p53 and subsequently enhance MDM2-mediated p53 degradation 21,40 or suppress p53 transcriptional activity. 41 Our study of FBXW7-mediated Aurora B degradation indicates that a feedback loop exists to maintain the equilibrium between Aurora B, p53 and FBXW7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, the FBXW7-Aurora B link will be an important molecular target for rational cancer therapy. Since FBXW7 expression p53 and subsequently enhance MDM2-mediated p53 degradation 21,40 or suppress p53 transcriptional activity. 41 Our study of FBXW7-mediated Aurora B degradation indicates that a feedback loop exists to maintain the equilibrium between Aurora B, p53 and FBXW7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that Aurora B is a kinase that can negatively regulate p53 stability. 21 Because the stability of both p53 and Aurora B is regulated through ubiquitination, ubiquitin-mediated stabilization could play an important role for coordinating this inverse relationship. We examined whether FBXW7, a p53 target gene product and an E3 ubiquitin ligase component, has a biological impact on Aurora B.…”
Section: Fbxw7mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Aurora B kinase phosphorylates p53 at S183, T211, and S215 to accelerate the degradation of p53 through the polyubiquitination-proteasome pathway, thus functionally suppressing the expression of p53 target genes involved in cell cycle inhibition and apoptosis. 7 Inhibition of Aurora B kinase contributes to the aneuploidy, loss of mitochondrial membrane potential, activation of caspase-9 followed by activation of caspase-3. 20,21 In a preclinical study, the inhibition of Aurora B kinase via AZD1152 was found to inhibit the growth of colon, lung and hematologic tumor xenografts in immunodeficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…The over-expressions of Aurora A and B kinases have been observed in many types of human cancer, including cervical cancer, ovarian cancer, breast cancer, colorectal cancer, and gastric cancer. [5][6][7][8] Aurora A kinase controls centrosome maturation, mitotic spindle formation, chromosomes segregation and the process of cytokinesis in mammalian cells. [9][10][11] Aurora A kinase affects DNA repair and thus controls the radio-and chemosensitivities of cancer cells.…”
Section: Introductionmentioning
confidence: 99%